Research on Physico-Chemical Properties of Diethyl Ether/Linseed Oil Blends for the Use as Fuel in Diesel Engines - Krzysztof Górski; Ruslans Smigins; Rafał Longwic (Energies, 2020)
Physico-chemical properties of diethyl ether/linseed oil (DEE/LO) fuel blends were empirically tested in this article for the first time. In particular, kinematic viscosity (ν), density (ρ), lower heating value (LHV), cold filter plugging point (CFPP) and surface tension (σ) were examined. For this research diethyl ether (DEE) was blended with linseed oil (LO) in volumetric ratios of 10%, 20% and 30%. Obtained results were compared with literature data of diethyl ether/rapeseed oil (DEE/RO) fuel blends get in previous research in such a way looking on differences also between oil types. It was found that DEE impacts significantly on the reduction of plant oil viscosity, density and surface tension and improve low temperature properties of tested oils. In particular, the addition of 10% DEE to LO effectively reduces its kinematic viscosity by 53% and even by 82% for the blend containing 30% DEE. Tested ether reduces density and surface tension of LO up to 6% and 25% respectively for the blends containing 30% DEE. The measurements of the CFPP showed that DEE significantly improves the low temperature properties of LO. In the case of the blend containing 30% DEE the CFPP can be lowered up to −24 °C. For this reason DEE/LO blends seem to be valuable as a fuel for diesel engines in the coldest season of the year. Moreover, DEE/LO blends have been tested in the engine research. Based on results it can be stated that the engine operated with LO results in worse performance compared with regular diesel fuel (DF). However, it was found that these disadvantages could be reduced with DEE as a component of the fuel mixture. Addition of this ether to LO improves the quality of obtained fuel blends. For this reason, the efficiency of DEE/LO blend combustion process is similar for the engine fuelled with regular diesel fuel. In this research it was confirmed that the smoke opacity reaches the highest value for the engine fuelled with plant oils. However, addition of 20% DEE reduces this emission to the value comparable for the engine operated with diesel fuel.